Graduate Education in Humanities Computing. - Rockwell, Geoffrey (Computers & the Humanities, 2003)
The article focuses on developing graduate programs that are designed to produce masters of digital humanities. Humanities computing is shifting from an interdisciplinary field populated by amateurs to a specialized field with recognized degrees and credentials. A central problem in the development of these programs is the place of skills training. One solution is to add technical courses on electronic texts, markup, Web design, text programming, and so on. To get a digital humanities curriculum through university committees means running the gauntlet of humanities colleagues who believe there is no place for skills in the humanities, and computer science colleagues who believe the skills that are taught are unworthy of graduate credit.